Evaluation of oral hygiene behaviors and teeth condition of students in oral and dental health nursing course - Sönmez, Mehtap; Akben, Mine; Göçebe, Berna (Acta Scientiarum. Health Sciences, 2022)
Nursing students are role model related to health franchise play an important in oral health care and promotion. This study aim is assessment the caries and oral and dental health behaviors of nurse students who be able expected take upon the responsibility of oral health in future. This was descriptive observational study with cross‑sectional approach, conducted at a state university in Mediterranean, Turkey. The study population was formed from 34 nursing students who voluntary select to course of oral and dental health nursing. Firstly, data were collected by socio-demographic form and then all students had been examined by dentist researcher. It was determined that 76.5% of the nursing students included in the study had at least one tooth decay, 70.6% needed treatment, and 67.6% had debris. It was determined that there was a relationship between gender, floss use, mouthwash, regular brushing teeth twice a day before the age of 6, smoking, and D, F, M, DMFS, DMFT indices in those who were breastfed for >=6 months. Increasing the awareness level of students will have a positive impact on the health of the patients they will care for.